Generalized leaky integrate-and-fire models classify multiple neuron types - Corinne Teeter (Nature Portfolio, 2018)
Simplified neuron models, such as generalized leaky integrate-and-fire (GLIF) models, are extensively used in network modeling. Here the authors systematically generate and compare GLIF models of varying complexity for their ability to classify cell types in the Allen Cell Types Database and faithfully reproduce spike trains.